Fund Management for Zakat, Infaq and Sadaqah at BAZNAS Indramayu Regency - Fera Nurwidia Ningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
Zakat, infaq and shodaqoh are acts of worship that have a very strategic position in terms of religious, social, economic and community welfare aspects. Zakat is an obligation for Muslims to carry out the 3rd pillar of Islam which is the axis of the happiness of the servant in this world and in the hereafter. Through BAZNAS institutions, it is easier for the community to channel this third pillar of Islam. This type of research uses field research, research conducted by collecting data and information obtained directly from respondents and directly observing research objects related to research techniques. The research method used in this study is a type of field research using qualitative research methods. The results of the study concluded that the flow of BAZNAS activities in Indramayu Regency started with reception, recording and finally distribution. As for the zakat received, there are 3: zakat mal, zakat fitrah and zakat profession. This is in accordance with the legal basis of Law Number 23 of 2011 concerning Management of Zakat. The process of channeling the allocation of zakat, infaq and shodaqah funds at BAZNAS Indramayu Regency is divided into two, the first is incidental distribution and the second is collective distribution. Incidental distribution, namely distribution carried out after the opinion of the proposal from the community and BAZNAS Indramayu will process and follow up on the proposal based on predetermined requirements, then it will be forwarded to the leader regarding the proposal. If it has been received, BAZNAS will assist it. While collective distribution is usually through the sub-district UPZ (zakat recipient unit) for villages in the sub-district to channel the funds